KORELASI ANTARA PERIKSAAN DARAH SAMAR TINJA MENGGUNAKAN ANTI-HEMOGLOBIN MANUSIA DAN PENGAMATAN MIKROSKOPIS - Liana Liana; Prihatini Prihatini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
Test for occult blood in faeces is an important part of the early detection of colorectal cancer, gastrointestinal bleeding, and anaemia.Colorectal cancer is the second leading cause of cancer deaths in the United States. Immunochemistry method for detection of humanhaemoglobin in faeces has been developed. The advantages of this method are improving analytical sensitivity and specificity, alsoavoiding the dietary restrictions requirement, compared with benzidine test, and guaiacum test. A study was performed to correlate theresult of fecal occult blood by immunochemistry method using anti-human haemoglobin and microscopic examination of red blood cellsin faeces of outpatients in the Clinical Pathology Laboratory, Dr. Soetomo Hospital, Surabaya. Faeces of fifty one patients tested for fecaloccult blood were examined by immunochemistry method compared with microscopic examination of red blood cells. Comparison ofthe two methods was done by statistical analysis, Mc Nemar test. The correlation was measured using ROC curve. The results showed acorrelation between immunochemistry method and microscopic examination with average red blood cells (RBC) ≤ 2/hpf, p = 0.008; RBC≥ 3/hpf, p = 0.289. ROC curve showed r = 0.941. In conclusion, a significant correlation between positive results of immunochemistrymethod and microscopic examination with average red blood cells ≥ 3/hpf. Further research using larger and more representativesamples should be carried out.